The Role of NK Cells in Pig-to-Human Xenotransplantation - Gisella Puga Yung; Mårten K. J. Schneider; Jörg D. Seebach (Journal of Immunology Research)
Recruitment of human NK cells to porcine tissues has been demonstrated in pig organs perfused ex vivo with human blood in the early 1990s. Subsequently, the molecular mechanisms leading to adhesion and cytotoxicity in human NK cell-porcine endothelial cell (pEC) interactions have been elucidated in vitro to identify targets for therapeutic interventions. Specific molecular strategies to overcome human anti-pig NK cell responses include (1) blocking of the molecular events leading to recruitment (chemotaxis, adhesion, and transmigration), (2) expression of human MHC class I molecules on pECs that inhibit NK cells, and (3) elimination or blocking of pig ligands for activating human NK receptors. The potential of cell-based strategies including tolerogenic dendritic cells (DC) and regulatory T cells (Treg) and the latest progress using transgenic pigs genetically modified to reduce xenogeneic NK cell responses are discussed. Finally, we present the status of phenotypic and functional characterization of nonhuman primate (NHP) NK cells, essential for studying their role in xenograft rejection using preclinical pig-to-NHP models, and summarize key advances and important perspectives for future research.